Uploading speaking assignment to YouTube channel as an effort in increasing student’s pronunciation skill - Setya Putri Rahayu; Widyarini Susilo Putri (Universitas Merdeka Malang, 2018)
YouTube is an internet channel in which people can freely find, watch, and upload any videos without any particular regulation. Learning motivation can be achieved in many ways. One of those is by uploading speaking assignment to YouTube channel,and a lot of people can watch it. This can be a strong motivation of the students to practice their pronunciation as well as possible. The objective of this study was to investigate student’s motivation in learning pronunciation by uploading their speaking assignment to YouTube. The study employed qualitative study with descriptive analytical approach. Qualitative study was chosen to dig deeper information related to the focus of the study. The instrument of the study was an open questioner with 5 questions related to student’s motivation in learning pronunciation. The study applied random sampling technique with 10 informants who had submitted their speaking assignment to YouTube. The study showed that uploading speaking videos in YouTube could increase student’s motivation. 80 percent of the respondents revealed that before they made their videos, they prepared and rehearsed to have correct pronunciation. In conclusion, uploading video in you tube channel had increased student’s motivation in mastering English pronunciation. DOI: 10.26905/enjourme.v2i2.2741